Kedudukan Guru Sebagai Pendidik - jabri, Umiyati; Naro, Wahyuddin; Yuspiani, Yuspiani (Universitas Muhammadiyah Enrekang, 2023)
Abstract: This study aims to provide information about teachers as educators using library research research methods. In this study examines the position of teachers as educators. Teachers play a pivotal role in education and shaping the future of the younger generation. They are not just conveyors of knowledge, but also leaders, inspirers, and guides in students' learning journeys. In this abstract, we explore the significant role of teachers as educators and the impact they have on students. Through quality teaching, teachers become agents of change in transforming students' knowledge and skills. They also serve as facilitators of learning, creating an environment conducive to the development of critical thinking, creativity, and problem-solving skills. Teachers act as mentors, helping students understand ethics, morals, and social values. They also serve as evaluators of students' progress, providing constructive feedback for further development. Moreover, teachers serve as role models in attitudes and behaviors expected from students. They act as liaisons between schools, students, and communities, collaborating with stakeholders to create a conducive learning environment. In shaping the future, teachers have an irreplaceable role in guiding students towards success and a better quality of life. Abstrak: Penelitian ini bertujuan untuk memberikan informasi tentang guru sebagai pendidik dengan menggunakan metode penelitian library research. Pada penelitian ini mengkaji posisi guru sebagai pendidik. Guru memiliki peran sentral dalam pendidikan dan membentuk masa depan generasi muda. Mereka tidak hanya menyampaikan pengetahuan, tetapi juga berperan sebagai pemimpin, inspirator, dan pemandu dalam perjalanan belajar siswa. Dalam abstrak ini, kami menyelidiki peran penting guru sebagai pendidik dan dampak yang mereka berikan pada siswa. Melalui pengajaran yang berkualitas, guru menjadi agen perubahan dalam mentransformasi pengetahuan dan keterampilan siswa. Mereka juga berperan sebagai fasilitator pembelajaran, menciptakan lingkungan yang kondusif bagi siswa untuk mengembangkan keterampilan berpikir kritis, kreativitas, dan pemecahan masalah. Guru juga berfungsi sebagai pembimbing, membantu siswa memahami etika, moral, dan nilai-nilai sosial. Mereka juga menjadi penilai kemajuan siswa, memberikan umpan balik yang konstruktif untuk pengembangan lebih lanjut. Selain itu, guru menjadi model peran dalam sikap dan perilaku yang diharapkan. Mereka juga berperan sebagai penghubung antara sekolah, siswa, dan komunitas, bekerja sama dengan pemangku kepentingan lainnya untuk menciptakan lingkungan pembelajaran yang baik. Dalam rangka membentuk masa depan, guru memiliki peran yang tak tergantikan dalam membimbing siswa menuju kesuksesan dan kualitas hidup yang lebih baik.